The anti-arthritic activity of total glycosides from Pterocephalus hookeri, a traditional Tibetan herbal medicine - Shen, Xiao-fei (Pharm Biol, 2016)
Context:Pterocephalus hookeri (C. B. Clarke) Hock., a traditional Tibetan herbal medicine rich in glycosides, has been used to treat several diseases including rheumatoid arthritis. Objective: To evaluate the anti-arthritic activity of total glycosides from P. hookeri, and its possible mechanisms of action. Materials and methods: Anti-arthritic activity of total glycosides from P. hookeri (oral administration for 30 days at 14–56 mg/kg) was evaluated using paw swelling, arthritis scores and histopathological measurement in adjuvant-induced arthritis (AA) Sprague-Dawley rats. The NF-κB p65 expression in synovial tissues, and serum superoxide dismutase (SOD) activity, malondialdehyde (MDA) and nitric oxide (NO) levels was measured in AA rats, respectively. Further assessment of anti-inflammatory and analgesic activities of these glycosides were carried out using inflammation and hyperalgesia models induced by xylene, carrageenan, agar and acetic acid, respectively. Results: Total glycosides (56 mg/kg) decreased the paw swelling (38.0%, p < 0.01), arthritis scores (25.3%, p < 0.01) and synovial inflammation in AA rats. The glycosides significantly (p < 0.05–0.01) attenuated the inflammation induced by xylene, carrageenan, acetic acid and agar, increased the pain threshold in acetic acid-induced writhing in mice and mechanical stimuli-induced hyperalgia in AA rats. The glycosides (14, 28, 56 mg/kg) also suppressed the NF-κB p65 expression (33.1–78.2%, p < 0.05–0.01), reduced MDA (21.3–35.9%, p < 0.01) and NO (20.3–32.4%, p < 0.05–0.01) levels, respectively, enhanced the SOD activity (7.8%, p < 0.05) at 56 mg/kg in AA rats. Discussion and conclusion: Our findings confirmed the anti-arthritic property of the total glycosides from P. hookeri, which may be attributed to its inhibition on NF-κB signalling and oxidative stress.